Upaya Pencegahan dan Penanggulangan tindak Pidana Perdagangan Orang - Julius Mangatur; Parasian Simanungkalit; Anwar Sadat (Syntax Corporation, 2023)
This trafficking crime is usually not only committed by individuals but also carried out by a group of people (corporations). This form of trafficking is related to commercial sex work and the purpose of exploitation. Exploitation includes, exploitation of prostitution by others, or other forms of sexual exploitation, forced labor or service, slavery, or slavery-like practices, servitude or organ harvesting. The issue raised in this case is how the imposition of criminal sanctions in the Criminal Code and outside the Criminal Code and how these sanctions are related in the Human Rights Law in Law No. 39 of 1999. Based on Article 1 paragraph 1 of Law Number 21 of 2007 concerning Trafficking in Persons, the definition is the act of recruiting, transporting, sheltering, sending, transferring, or receiving a person by threat of violence, use of force, kidnapping, captivity, forgery, fraud, abuse of power or vulnerable position, debt bondage or giving payment or benefits, so as to obtain the consent of the person in control of the other person, whether carried out within countries or between countries, for the purpose of exploitation or resulting in exploitation of people. Trafficking operations were often conducted behind closed doors and operated outside the law. Traffickers quickly developed an undetectable way of working. This crime continues to grow at a rapid pace.